Revitalizing Kitab Kuning Instruction in Islamic Higher Education: Structural Challenges and Curriculum Integration - Suriani, Erma; Muliadi, Erlan; Nasri, Ulyan (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
The teaching of kitab kuning (classical Islamic texts) remains a defining yet increasingly marginalized component of Islamic higher education in Indonesia. This study examines the structural, pedagogical, and curricular factors shaping students’ turats literacy and explores strategies for revitalizing classical text instruction within contemporary university contexts. Using a qualitative multi-site case study design, data were collected during the 2024–2025 academic year through interviews, focus group discussions, classroom observations, document analysis, and a diagnostic assessment conducted at one state Islamic university and three private Islamic higher education institutions in West Nusa Tenggara. Qualitative data involved 19 informants comprising lecturers, students, and curriculum developers, while a separate diagnostic assessment was administered to 67 undergraduate students to evaluate proficiency in reading unvoweled Arabic texts. The findings indicate that a substantial proportion of students experience persistent difficulties in engaging independently with kitab kuning, which are closely associated with weak linguistic foundations, uneven lecturer competence, and the marginal positioning of classical texts within formal curricula. Clear contrasts were observed between state universities and institutions affiliated with ma’had or pesantren traditions, where sustained textual engagement supports stronger turats literacy. Based on these findings, the study proposes an integrative curriculum framework that embeds kitab kuning instruction across progressive stages of undergraduate education, aligns learning outcomes and assessment with direct textual engagement, and strengthens lecturer qualification standards, contributing an empirically grounded model for revitalizing turats literacy in Islamic higher education.